Traditional Ethics as the Foundation of Da'wah Management: Analysis of the Implementation of Cultural Values in Religious Organisations (Case Study of Nahdlatul Ulama)/Etika Tradisi sebagai Fondasi Manajemen Dakwah: Analisis Implementasi Nilai-Nilai Budaya dalam Organisasi Keagamaan (Studi Kasus Nahdlatul Ulama) - Rohman; Nadia Cahaya Amanda; Muhammad Hafizul Arifin (P3M STID Mustafa Ibrahim Al-Ishlahuddiny Kediri Lombok Barat, 2025)
This study analyses the implementation of traditional ethical values as the foundation of da'wah management in the Nahdlatul Ulama (NU) organisation. As the largest Islamic organisation in Indonesia with more than 90 million members, NU is unique in integrating the traditional ethical values of Ahlussunnah Wal Jamaah with modern da'wah management practices. This study uses a qualitative approach with a case study method, collecting data through in-depth interviews with NU administrators and clerics, observation of organisational activities, and documentation studies. The results show that the values of tawassuth, tasamuh, tawazun, and amar ma'ruf nahi munkar form the philosophical foundation that distinguishes NU's management from other modern organisations. These values are operationalised through the dualistic leadership system of Syuriah-Tanfidziyah, the Bahtsul Masail mechanism, and the use of classical Islamic texts as a source of legitimacy for decisions. The principle of al-muhafadhah 'ala al-qadim al-shalih allows NU to maintain the pesantren tradition while adopting modern technology in its da'wah. The concepts of adab and ta'dhim create an informal hierarchy based on scientific seniority that strengthens organisational cohesiveness. The main challenges faced are harmonising the flexibility of tradition with the demands of modern management standardisation, as well as generational conflicts between senior clerics and young activists. This research contributes to the development of a humanistic and sustainable local wisdom-based da'wah management model and provides alternatives for religious organisations in optimising tradition-based management in the contemporary era. Penelitian ini menganalisis implementasi nilai-nilai etika tradisi sebagai fondasi manajemen dakwah dalam organisasi Nahdlatul Ulama (NU). Sebagai organisasi Islam terbesar di Indonesia dengan lebih dari 90 juta anggota, NU memiliki keunikan dalam mengintegrasikan nilai-nilai etika tradisi Ahlussunnah Wal Jamaah dengan praktik manajemen dakwah modern. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus, mengumpulkan data melalui wawancara mendalam dengan pengurus NU dan kiai, observasi kegiatan organisasi, serta studi dokumentasi. Hasil penelitian menunjukkan bahwa nilai-nilai tawassuth, tasamuh, tawazun, dan amar ma'ruf nahi munkar menjadi fondasi filosofis yang membedakan manajemen NU dengan organisasi modern lainnya. Nilai-nilai ini dioperasionalisasikan melalui sistem dualisme kepemimpinan Syuriah-Tanfidziyah, mekanisme Bahtsul Masail, dan penggunaan kitab kuning sebagai sumber legitimasi keputusan. Prinsip al-muhafadhah 'ala al-qadim al-shalih memungkinkan NU mempertahankan tradisi pesantren sambil mengadopsi teknologi modern dalam dakwahnya. Konsep adab dan ta'dhim menciptakan hierarki informal berbasis senioritas keilmuan yang memperkuat kohesivitas organisasi. Tantangan utama yang dihadapi adalah harmonisasi antara fleksibilitas tradisi dengan tuntutan standardisasi manajemen modern, serta konflik generasi antara kiai senior dengan aktivis muda. Penelitian ini berkontribusi pada pengembangan model manajemen dakwah berbasis kearifan lokal yang humanis dan berkelanjutan, serta memberikan alternatif bagi organisasi keagamaan dalam mengoptimalkan manajemen berbasis nilai-nilai tradisi di era kontemporer.